The Main Ionization Sources of Gas in Several Nearby Star Forming Galaxies - Behjat Zarei Jalalabadi; Abbas Abedi; Alexei Moiseev (Iranian Journal of Astronomy and Astrophysics)
The emission-line intensity ratios are used to distinguish the main sources of gas ionization to study the state of galactic interstellar medium (ISM). In intermediate cases, when the contributions of radiation from OB stars and from shock waves mix, the identification becomes uncertain. As an extra parameter, the gas velocity dispersion in the line-of-sight can be added to classical diagnostic diagrams (i.e., "BPT-σ" relations) to help finding an appropriate solution. The minimum distance from the curve that bounds the H II-type ionization region for each point in BPT-ρ diagram can be used to characterize the excitation mechanism of the ionized gas. The shock excitation in the diffuse ionized gas (DIG) can be realized by the correlation between ρ and σ, while the H II regions with low level turbulent motions can be characterized by the absence of this correlation. We consider the "BPT-σ" relation and the correlation between σ and ρ to determine the ionized gas excitation in several nearby star-forming galaxies. Distributions of the velocity dispersion are obtained from the scanning Fabry-Perot interferometer observations at the SAO RAS 6-m telescope, whereas the emission-line ratios are calculated from the archival long-slit spectroscopic data. The results of this study are reported for Mrk 370, NGC 4068, UGC 8313, and UGC 8508.